Effect of 8-Week Resistance Training on Hypertrophy, Strength, and Myostatin Concentration in Old and Young Men - Raoof Negaresh; Roohollah Ranjbar; Mohammad Mo'men Gharibvand; Abdolhamid Habibi; Motahare Moktarzade (University of Social Welfare & Rehabilitation Sciences, 2017)
Objectives The decline in muscle mass and strength, which are associated with aging, is called sarcopenia. Resistance training is one of the effective methods to deal with sarcopenia. Correspondingly, this study aimed to investigate the effect of 8-week resistance training on muscle mass, strength, and myostatin concentration in old and young men. Methods & Materials The present study included 14 old men (age range of 55 to 70 years) and 11 young ones (age range of 20 to 35 years) who were randomly chosen from the volunteers. They participated in a progressive resistance training (gradual increase in training load, 50% of one repetition maximum in the first week to 85% in the eighth week) for 8 weeks, 3 days a week. Daily calorie intake, strength, muscle mass, muscle cross-sectional area (by CT scan), and myostatin concentration were measured before and after the training. Results The findings of the study indicated that after 8 weeks of training, muscle strength significantly increased in the old group in comparison with the young group (P<0.05); however, total muscle mass significantly increased in the young one (P<0.05). Daily calorie intake did not change in both groups (P>0.05). Quadriceps muscle mean (SD) cross-sectional area of the young group (pretest: 76.03[12.21] cm2 compared to posttest: 79.16[11.54] cm2) significantly increased (P<0.05) compared to that in the old group (pretest: 60.03[10.57] cm2 compared to posttest: 61.93[10.43] cm2). The myostatin mean (SD) concentration significantly decreased in both groups (P<0.05), but there was no difference between the groups (3.86[1.89] ng/mL and 3.68[1.66] ng/mL in elderly and young group, respectively; P > 0.05). Also, there was a significant correlation between myostatin concentration with muscle mass in old men (r=0.73, P<0.05). Conclusion Resistance training was associated with a decline in myostatin level and increase in the muscle mass and cross-sectional area. Hence, the beneficial effect of resistance training may decrease age-related muscle atrophy and affect elderly health.